Thermal cotreatment of municipal solid waste incineration fly ash with sewage sludge: Phases transformation, kinetics and fusion characteristics, and heavy metals solidification. (1st October 2021) - Lin, Xiaoqing; Mao, Tieying; Chen, Zhiliang; Chen, Jie; Zhang, Sheng; Li, Xiaodong; Yan, Jianhua
Abstract: Thermal treatment is an effective method to detoxicate municipal solid waste incineration (MSWI) fly ash (FA) and then produce secondary materials for recycling, but the development of this method is limited by the high energy cost. In this study, two typical types of FA are proposed to be thermally cotreated with sewage sludge (SS), respectively, to reduce energy consumption and control the risk of heavy metals leaching. The SiO2 and Al2 O3 with high content in SS were prone to react with compounds ( e.g., Na2 O, MgO, and CaO) in FA to form low-melting-temperature eutectics, such as NaAlSi3 O8 and CaMgSi2 O6, greatly reducing the ash fusion temperatures (AFT) by up to 182 °C. Mixtures with 45 wt% FA showed the greatest reduction on AFT compared to mixtures with 15 and 30 wt% FA. Also, the kinetics analysis based on TG/DSC results in conjunction with Avrami–Erofeev model showed that the apparent activation energy of mixtures of FA and SS ( i.e., 561.4 ± 110.6 kJ/mol) was obviously lower than that of FA ( i.e., 660.0 ± 12.9 kJ/mol). Thermal cotreatment of FA with SS significantly increased the removal efficiency of chlorine from 23.5 to 66.52 wt% to 80.5–98.2 wt% by facilitating the reactions releasing HCl, which is beneficial for utilizing the generated products as construction materials. Heavy metals in the solid residues from thermal cotreatment of FA and SS were effectively solidified via ion exchange into Ca-bearing minerals or aluminosilicates, and the leaching concentrations of Cd, Cr, Cu, Ni, Pd, and Zn mostly well met the standards for utilization as construction and building materials in China. Highlights: Thermal cotreatment of fly ash with sewage sludge reduced the ash fusion temperatures by up to 182 °C. Mixtures of fly ash and sewage sludge had lower apparent activation energy than fly ash. Removal of Cl from fly ash was significantly improved by thermally cotreating with sewage sludge. High content of Si/Al-compounds in sewage sludge facilitated the solidification of heavy metals.